Economic dimension of India’s foreign policy towards Russia: Late 20th- early 21st century - Rahman, Md. Sayedur; Tul-Kubra, Shakila (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
In the international framework India is finding a larger position for itself. This hope is focused on the belief that India is a prosperous democracy with substantial human and material resources; it is an increasingly strong economic power; it has a proven record as a responsible and law-abiding regime, and as a member of the non-aligned party it has consistently shared the interests of the developing nations. Indian foreign policy makers argue that India wants to re-invent itself at this point of 'take-off' as a great force. India needs new alliance for the proposed new position, including the dominant superpower, the United States of America (US). The US has said it would turn India into a great force. This essay attempts to examine the old pattern of relations with Russia that India had enjoyed. There's an Indo-US triangular alliance taking its place. How is this current type of strategic partnership distinct from that of the Indo Soviet/ Russian alliance? However, both countries' natural desire to strive towards multi polarity in world politics has helped restore the relationship, particularly over the past decade. Remarkably, ties with the US no longer stand in the way of stronger relations between India and Russia. The turbulent security climate marked by what is frequently assumed to be the state-sponsored insurgency invulnerable Asian areas, the war in Afghanistan, and the political turmoil in both Afghanistan and Central Asian countries has paved the way for a strategic alliance between India and Russia.